Conceptualising Regional Power in International Relations: Lessons from the South African Case - Daniel Flemes (German Institute of Global and Area Studies (GIGA), 2007)
Regional powers can be distinguished by four pivotal criteria: claim to leadership, power resources, employment of foreign policy instruments, and acceptance of leadership. Applying these indicators to the South African case, the analysis demonstrates the crucial significance of institutional foreign policy instruments. But although the South African government is ready to pay the costs of co-operative hegemony (such as capacity building for regional institutions and peacekeeping), the regional acceptance of South Africa's leadership is constrained by its historical legacy. Additionally, Pretoria's foreign policy is based on ideational resources such as its reputation as an advocate of democracy and human rights and the legitimacy derived from its paradigmatic behaviour as a 'good global citizen'. However, the Mbeki presidency is more successful in converting these resources into discursive instruments of interest-assertion in global, rather than in regional bargains. In effect the regional power's reformist South-oriented multilateralism is challenging some of the guiding principles of the current international system. – – Regionale Führungsmächte können anhand von vier Kriterien unterschieden werden: Artikulation des Führungsanspruchs, verfügbare Machtressourcen, außenpolitische Instrumente zur Interessendurchsetzung und Akzeptanz des Führungsanspruchs durch externe Akteure. Die Übertragung dieser Kriterien auf den südafrikanischen Fall zeigt zunächst die zentrale Bedeutung institutioneller Instrumente innerhalb der südafrikanischen Außenpolitik. Obgleich Pretoria bereit ist, die Kosten kooperativer Hegemonie zu tragen (z.B. Investitionen in Regionalinstitutionen und Friedenssicherung), untergräbt das historische Legat der Ära der Apartheid den regionalen Führungsanspruch. Dabei basiert die Außenpolitik des demokratischen Südafrika zuvorderst auf ideellen Ressourcen: Als Anwalt für Demokratie und Menschenrechte hat Südafrika seit dem Regimewechsel viel Renommee und Legitimität erworben. Die Konvertierung dieser ideellen Ressourcen in diskursive Instrumente zur Interessendurchsetzung gelingt der Regierung Mbeki in globalen Verhandlungen allerdings weitaus besser als in afrikanischen Institutionen. Im Ergebnis stellt der reform- und entwicklungsorientierte Multilateralismus der südafrikanischen Regionalmacht einige etablierte Normen des gegenwärtigen internationalen Systems in Frage.
Keywords: 300; South Africa; regional power; foreign policy; co-operative hegemony; multipolarisation of the international system